The intensive capitalization of the Romanian agricultural potential - Bucur, Ion; Bucur, Bogdan (Economics of Agriculture, 2010)
This article emphasizes the high agricultural potential that Romania has and its low utilization. Even though Romania has terrains that can be used in agriculture, around 62% of the total country surface and has around 30% of the active population involved in agriculture, it is a net importer of agricultural products. Not only that, but the agricultural cultures have a high vulnerability to the evolution of the weather, the irrigational system and the level of mechanization being underdeveloped. By increasing the use percentage of agricultural terrains and trough expanding the ecological farming, agricultures contribution to the development of new working places, improving the commercial balance and the general stimulation of the economic growth will be increased.